Pengaruh Dana Pihak Ketiga, Capital Adequacy Ratio, Return nn Asset, Net Interest Margin dan Non Performing Loan Terhadap Penyaluran Kredit Bank Umum di Indonesia - Pratiwi, Susan; Hindasah, Lela (Jurnal Manajemen Bisnis, 2014)
This research aim to measure impact of internal variable like DPK, CAR, ROA, NIM and NPL toward credit distribution of Commercial Banks in Indonesia. The objects of this research is Banking population because base on Banking function that is intermediation among parties that excess funding with the party that need funding. The population in this research was all commercial Banks during period of January 2009 until December 2013 by using secondary data in the form of time series, totally there are 60 data in a month. Methods used is a Error Correction Model (ECM) in e-views for measuring variable influence towards internal Banking credit distribution in the long term and the short term. The result of this research showed that internal factors (DPK, CAR, ROA, NIM and NPL) used as the independent variable having influence simultaneously and significantly to credit distribution. Variable DPK have positive influence and significant to credit distribution, while for variables each CAR and ROA variables are not have negative influence on credit distribution and of it self. On the other side, for variables NPL have negative influence and significant to credit distribution.